2012
DOI: 10.1002/cne.23014
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral and ipsilateral ascending tectopulvinar pathways in mammals: A study in the squirrel (spermophilus beecheyi)

Abstract: The mammalian pulvinar complex is a collection of dorsal thalamic nuclei related to several visual and integrative processes. Previous studies have shown that the superficial layers of the superior colliculus project to multiple divisions of the pulvinar complex. Although most of these works agree about the existence of an ipsilateral tectopulvinar projection arising from the stratum griseum superficialis, some others report a bilateral projection originating from this same tectal layer. We investigated the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 93 publications
7
46
0
Order By: Relevance
“…Major et al (2000) have proposed that in the squirrel, parabigeminal axons are directed to the bottlebrush endings of the TGCs, which send a non-topographic, bilateral projection to the caudal pulvinar in the thalamus, just like Rtprojecting TGCs in birds (Major et al, 2000, Fredes et al, 2011. The parabigeminal axons might exert similar control of the collicular-caudal pulvinar pathway as shown here for birds.…”
Section: Stimulus Selection Within Rt Receptive Fieldsmentioning
confidence: 64%
“…Major et al (2000) have proposed that in the squirrel, parabigeminal axons are directed to the bottlebrush endings of the TGCs, which send a non-topographic, bilateral projection to the caudal pulvinar in the thalamus, just like Rtprojecting TGCs in birds (Major et al, 2000, Fredes et al, 2011. The parabigeminal axons might exert similar control of the collicular-caudal pulvinar pathway as shown here for birds.…”
Section: Stimulus Selection Within Rt Receptive Fieldsmentioning
confidence: 64%
“…1 B, C). Our previous work demonstrated that these signals result from synaptic activity (Vokoun et al, 2010) and our more recent work shows that the spread of activation from intermediate layers into the superficial layers is mediated by a novel excitatory pathway from the stratum griseum intermediale (SGI; intermediate layers) to the stratum griseum superficiale (SGS; superficial layers; Ghitani et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…A second possibility is that the superficial layers of the SC play a role in action selection when faced with options. Indeed, information from the motor layers of the SC encoding the location of the two potential targets could activate a single region within the sensory layers of the SC through a newly identified, ascending excitatory pathway (Ghitani et al, 2012). This activation would result in potentiating the activity of visual pathways through the projections of superficial layer neurons to the lateral geniculate nucleus and the pulvinar (Diamond et al, 1991;Chomsung et al, 2008;Fredes et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurons that innervate the dLGN are always located in the upper onehalf of the stratum griseum superficiale (SGS) and the majority of these cells are narrow field vertical cells (NFV), whereas those neurons that project to the pulvinar are located in the lower half of the SGS and stratum opticum (SO), and the majority of these cells are wide field vertical cells (WFV) (Mooney et al, 1988;Fredes et al, 2012;Gale and Murphy, 2014). It has also been noted that the somata of tectopulvinar cells are larger than those of tectogeniculate neurons (Albano et al, 1979;Kawamura et al, 1980;Caldwell and Mize, 1981;Graham and Berman, 1981;Harrell et al, 1982).…”
Section: Tectothalamic Cellsmentioning
confidence: 99%